The pre and post assessment of glycemic control and patients’ medication adherence of Type 2 diabetes mellitus (T2DM) in pharmacist-managed DMTAC program at Putrajaya Health Clinic / Hajar Mat Noji - Mat Noji, Hajar (2017)
According to WHO 2014 data, 9% of adults 18 years and older had diabetes. In 2012 diabetes was the direct cause of 1.5 million deaths. Until this date, diabetes mellitus has become a major healthcare burden in almost all countries in the world. According to the Third National Health and Morbidity Survey (2006) done by the Ministry of Health Malaysia, the prevalence of diabetes among Malaysian adults of over 30 years has almost increased by two folds. WHO states that non-adherence to medications is a major problem whereby poor adherence can lead to negative health outcomes such as worsened disease or even mortality. The aim of this study was to evaluate the effectiveness of pharmacist-managed DMTAC program in improving patients’ glycemic control, lipid profile, and medication adherence pre and at least 3 months post DMTAC program. This retrospective cross sectional study was carried out within 3 months at the out-patient pharmacy of Putrajaya Health Clinic Presint 9. Primary outcome measure was the glycemic control changes pre and post DMTAC service. Other relevant clinical parameters changes were the secondary outcome measures. There was a significant difference of mean HbA1c by -0.82%, which decreased from 10.46% (S = 1.68) to 9.64% (SD = 2.34) (p<0.001). Meanwhile, the reduction of 2.9 mmol/L (p<0.001) in mean FBG was also significant. This statistical significant difference of HbA1c indicates a positive impact of DMTAC program.